Evaluating intersectional variation of HPV-associated cancers in rural America - Jason Semprini; Gabriel Benavidez; Whitney E. Zahnd; Heather M. Brandt (BMC Public Health)
Abstract Purpose For decades, incidence of human papillomavirus (HPV)-associated cancers has been increasing in rural communities across the United States. Although emerging evidence shows a widening rural-urban disparity, rural intersectionality has been understudied. Our study examined the incidence of HPV-associated cancers within rural communities to identify differences by race/ethnicity for males and females, and explore how these differences varied by cancer type, socioeconomic, and geographic factors. Methods We accessed age-adjusted cancer incidence rates (2010–2019) from the North American Association of Central Cancer Registries (NAACCR) for HPV-associated cancers (cervical, vaginal, vulvar, penile, anal, oropharyngeal) in rural counties. Stratifying by sex, we calculated incidence rate ratios by race/ethnicity. Subgroup analyses included age, site, census-tract poverty, census tract socioeconomics, and region. Results Between 2010 and 2019, rural HPV-associated cancer was 11.8 cases per 100,000 population. We found significant heterogeneity within male (10.5) and female (13.2) rates. For males, the lowest rate was found in non-Hispanic Asian-American/Pacific-Islander populations (3.7) and Hispanic populations (4.8), and the highest rate was found in non-Hispanic White populations (11.2). For females, the lowest rate was also found in Hispanic Asian-American/Pacific-Islander populations (8.8) and the highest rates were found in non-Hispanic Black (13.8) and non-Hispanic American Indian/Alaska Native populations (14.5). However, these racial/ethnic differences varied across rural subpopulations, geography, and poverty. Conclusions Appreciating the diversity of the rural cancer burden can be used to effectively develop and implement public health interventions to address HPV-related cancer disparities in rural communities. Actions are needed to prioritize reducing the burden of HPV-associated cancer in AIAN populations in high-poverty rural communities.